KONSTRUKSI SOSIAL KEMANDIRIAN PEREMPUAN DI ERA GLOBALISASI (STUDI FENOMENOLOGI PEREMPUAN PENGEMUDI OJEK ONLINE DI KOTA SURABAYA) - Aura Afan Shabrina; Sarmini Sarmini (Kajian Moral dan Kewarganegaraan, 2023)
Social construction always identifies the role of women only as good wives and mothers. However, the current of globalization has forced women out of the shackles of the domestic sphere and work in the public sphere, one of which is by becoming an online motorcycle taxi driver. This study aims to reveal the social construction of women's independence in the era of globalization which is associated with the factors forming social construction in society. There were four informants whose identities were deliberately disguised. The informants were taken based on evidence that the person concerned does indeed work as an online motorcycle taxi driver, is a woman who has or has been married, and those who have not or already have children. The focus of this research is to find out the social construction of women's independence in the era of globalization in the view of women online motorcycle taxi drivers associated with the factors forming social construction in society. Data collection techniques used include in-depth interviews, passive participant observation, and documentation. Data taken by in-depth interviews were then analyzed qualitatively. The results of this study indicate that there are three forms of women's independence in the era of globalization according to women online motorcycle taxi drivers, firstly the independence of working as an online motorcycle taxi driver as an alternative job, secondly in making decisions when facing sexual harassment at work, and thirdly making decisions related to the role of a mother in parenting. baby. Of the three forms of independence, the independence that is realized by working as an online motorcycle taxi driver and making decisions as a mother in caring for children is considered a little out of the order of community values. Meanwhile, there are no norms for the three forms of independence that lead to a violation of norms. Keywords: social construction, women, independence, online motorcycle taxi drivers